Neonates born to mothers with immune thrombocytopenia: 11 years experience of a single academic center. Issue 6 (September 2018) - Karakurt, Neslihan; Uslu, İlker and Albayrak, Canan and Tomak, Leman and Ozyazici, Elif and Albayrak, Davut and Aygun, Canan
Abstract : N/A: A major problem associated with immune thrombocytopenic purpura (ITP) in pregnancy is neonatal thrombocytopenia. We analyzed newborns born to mothers with ITP and examined predictive factors for thrombocytopenia. This retrospective study was performed in a single academic center from January 2007 to January 2018. Pregnant women with ITP and their babies are included. All neonates had a complete blood count and cranial ultrasound (USG) performed. Twenty seven neonates of 22 mothers were evaluated. A total of 23 (85%) of neonates were thrombocytopenic (<150 × 10 9 /l) and in 20 (74%) platelet count was below 50 × 10 9 /l. Median platelet count was 30 (4–300) × 10 9 /l. One baby experienced intracranial hemorrhage, eight (29.6%) had minor bleeding. When babies with and without minor bleeding were compared; no significant difference was found regarding maternal age, duration of ITP, lowest and 'before delivery' platelet count, treatment during pregnancy and splenectomy. Cutoff value of platelet count for bleeding was calculated as 27 × 10 9 /l with a sensitivity of 0.88 and specifity of 0.79. Strong correlation for postnatal thrombocytopenia was detected among siblings. Although the incidence of neonatal thrombocytopenia might be high, the incidence of poor neonatal outcomes is extremely low. Neonatal thrombocytopenia does not rely on maternal profile. The occurrence of neonatal thrombocytopenia and bleeding may be a risk factor for subsequent pregnancies. We suggest that the cutoff value for neonatal platelet count for bleeding can be used for management and treatment of neonates born to mothers with ITP.